« Le rossignol trouvera bon de parler lui-même de soi-même ». Discours animal et subversion libertine dans les États et Empires de la Lune et du Soleil de Cyrano de Bergerac - Aude Volpilhac (Itinéraires)
“Antispeciesism” is a concept forged in the twentieth century, but its polemical and paradoxical scope already emerged in the sixteenth and even more so in the seventeenth century, notably under the pen of Cyrano de Bergerac in Les États et Empires de la Lune et du Soleil. Fiction, which is at the core of his imaginary journey, supported by a subversive imagination freed from any constraint, opens up the field of possibilities allowing us to meet talking birds. But here we are far from the apparently agreed framework of the apologue, for making animals true literary characters, like men, is meaningful. Indeed, conferring logos on an animal is a paradoxical and subversive act in the seventeenth century, as it calls into question commonly accepted opinions—inherited from Aristotelianism and Christianity—on the hierarchy of beings and the supremacy of man within the living world. Making the animal speak first leads the reader to shift his gaze. Fiction shows us what reality robs us of, that is, animal interiority: not only are animals gifted with speech, and therefore with reason, but they do also possess a soul, two attributes that men, since antiquity, have attributed to themselves exclusively. To have the animal speak like a man is first of all to push man to recognise that the animal is a man like any other. In this respect, Cyrano's animal discourse interweaves narrative, stylistic and enunciative issues on the one hand, with polemical, philosophical and ethical ones on the other.